2014
DOI: 10.5539/res.v6n1p171
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-Efficacy as Determinant of Students’ Attitudes toward School: A study at the School Level

Abstract: Teachers' self-efficacy was examined as determinant of students' attitudes toward school. Over 679 teachers and 1820 students in 23 Jordanian (primary and junior) schools were selected using simple random sampling. The instrument used in this study is Norwegian teachers' self-efficacy scale which was developed by Skaalvik and Skaalvik (2007) and students' attitudes toward school scale which was designed by the researchers. Results indicated that the level of teachers' self-efficacy is moderate. Also, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This corroborated our initial hypothesis that attitudes towards education would provide an independent contribution to individuals' career decision self-efficacy, which resonates with previous findings that indicate how recognizing the value and relevance of present opportunities for one's future is associated with different aspects of career decision--making, including career decision self-efficacy (Walker & Tracey, 2012). Furthermore, our results also confirm previous studies that demonstrated how individuals' attitudes towards school and their perception of relevance of education impact educational attainment and motivation, as well as the formulation of expectations towards the future (Al-Alwan & Mahasneh, 2014;McNeely et al, 2002;Raboteg et al, 2009;Smith & Sandhu, 2004;Whitlock, 2006), as they also indicate associations between attitudes towards education and academic achievement as well as mastery and performance achievement goals.…”
Section: Discussionsupporting
confidence: 90%
“…This corroborated our initial hypothesis that attitudes towards education would provide an independent contribution to individuals' career decision self-efficacy, which resonates with previous findings that indicate how recognizing the value and relevance of present opportunities for one's future is associated with different aspects of career decision--making, including career decision self-efficacy (Walker & Tracey, 2012). Furthermore, our results also confirm previous studies that demonstrated how individuals' attitudes towards school and their perception of relevance of education impact educational attainment and motivation, as well as the formulation of expectations towards the future (Al-Alwan & Mahasneh, 2014;McNeely et al, 2002;Raboteg et al, 2009;Smith & Sandhu, 2004;Whitlock, 2006), as they also indicate associations between attitudes towards education and academic achievement as well as mastery and performance achievement goals.…”
Section: Discussionsupporting
confidence: 90%
“…Existing research on teacher self-efficacy demonstrates that there is a connection between the self-efficacy beliefs of a teacher and the teacher's motivation and behavior within the classroom (Akkuzu, 2014;Skaalvik & Skaalvik, 2010;Tschannen-Moran & Hoy, 2007;Tschannen-Moran & Johnson, 2011;Tschannen-Moran & McMaster, 2009). There is also evidence that teacher self-efficacy can impact student behaviors and achievement outcomes (Al-Alwan & Mahasneh, 2014;Mojavezi & Tamiz, 2012;Pan, 2014;Tai, Hu, Wang, & Chen, 2012) and teachers with higher self-efficacy are more likely to devote time to instructional activities rather than classroom discipline (Phan & Locke, 2015). According to Zee and Koomen (2016) teachers who feel self-efficacious are more likely to have students who exhibit more on-task behavior, show increased engagement, and display more positive attitudes and motivations toward learning and going to school.…”
Section: Importance Of Teacher Self-efficacymentioning
confidence: 99%
“…However, in their role within the teacher evaluation process, the administrators also can have an effect on the learning environment through their ability to impact teachers' sense of efficacy. In order for this to happen administrators must first understand and accept the critical role that teacher self-efficacy plays in both teacher effectiveness and student achievement (Akkuzu, 2014;Al-Alwan & Mahasneh, 2014;Mojavezi & Tamiz, 2012;Skaalvik & Skaalvik, 2007). They must also develop a deep understanding of the sources of efficacy information that serve to build one's level of self-efficacy, namely mastery experiences, verbal persuasion, vicarious experiences, and emotional arousal.…”
Section: Implications For Practicementioning
confidence: 99%
“…Teacher self-efficacy belief is a significant variable in increasing the quality of education, in classroom management, in increasing student achievement, in the use of method and strategy and in increasing student motivation and success (Woolfolk et al, 1990;Al-Alwan and Mahasneh, 2014;Tschannen-Moran and Hoy, 2007).…”
Section: Introductionmentioning
confidence: 99%